Специализация к паразитизму клещей Bakericheyla chanayi (Trombidiformes, Cheyletidae) - Горголь, В.Т. (Вестник зоологии, 1982)
A cheyletoid mite, Bakericheyla chanayi, is studied for certain problems of its hostal, topographic and seasonal adaptation to parasitism on a bird's body.